Rhizobacteria-mediated resistance against the blackeye cowpea mosaic strain of bean common mosaic virus in cowpea (Vigna unguiculata) - Udaya Shankar, Arakere Chunchegowda; Chandra Nayaka, Siddaiah; Niranjan-Raj, Sathyanarayana; Bhuvanendra Kumar, Hanumanthaiah; Reddy, Munagala S; Niranjana, Siddapura Ramachandrappa; Prakash, Harishchandra Sripathy (Pest management science, 2009)
BACKGROUND: The present study investigated the effect of seven Bacillus-species plant-growth-promoting rhizobacteria (PGPR) seed treatments on the induction of disease resistance in cowpea against mosaic disease caused by the blackeye cowpea mosaic strain of bean common mosaic virus (BCMV).RESULTS: Initially, although all PGPR strains recorded significant enhancement of seed germination and seedling vigour, GBO3 and T4 strains were very promising. In general, all strains gave reduced BCMV incidence compared with the non-bacterised control, both under screen-house and under field conditions. Cowpea seeds treated with Bacillus pumilus (T4) and Bacillus subtilis (GBO3) strains offered protection of 42 and 41% against BCMV under screen-house conditions. Under field conditions, strain GBO3 offered 34% protection against BCMV. The protection offered by PGPR strains against BCMV was evaluated by indirect enzyme-linked immunosorbent assay (ELISA), with lowest immunoreactive values recorded in cowpea seeds treated with strains GBO3 and T4 in comparison with the non-bacterised control. In addition, it was observed that strain combination worked better in inducing resistance than individual strains. Cowpea seeds treated with a combination of strains GBO3 + T4 registered the highest protection against BCMV.CONCLUSION: PGPR strains were effective in protecting cowpea plants against BCMV under both screen-house and field conditions by inducing resistance against the virus. Thus, it is proposed that PGPR strains, particularly GBO3, could be potential inducers against BCMV and growth enhancers in cowpea.